Catalytic Synthesis of the Biofuel 5-Ethoxymethylfurfural (EMF) from Biomass Sugars - Dayong Yu; Xiaofang Liu; Jingjing Jiang; Yixuan Liu; Jinyu Tan; Hu Li (Journal of Chemistry)
A new generation of bioplatform molecule 5-ethoxymethylfurfural (EMF) has excellent energy density and combustion performance, which makes it a potential fuel additive. This article reviews the factors that affect the production of EMF from different feedstocks, including platform compounds, monosaccharides, polysaccharides, and raw lignocellulosic biomass. Focus is placed on discussing the catalytic efficiency with pros and cons of different acid catalysts, including homogeneous catalysts (i.e., liquid acids and metal salts), heterogeneous catalysts (i.e., zeolites, heteropolyacid-based hybrids, and SO3H-based catalysts), ionic liquids, mixed acid catalysts, and deep eutectic solvents (DESs). Except for the commonly used ethanol solvent, this review also summarizes the influence of the cosolvent system (e.g., ethanol/dimethylsulfoxide (DMSO), ethanol/tetrahydrofuran (THF), and ethanol/γ-valerolactone (GVL)) on the EMF yield.